The potential of natural products use in fused deposition modeling 3D printing of pharmaceutical dosage forms - Čanji Panić, Jelena; Todorović, Nemanja; Stjepanović, Ana; Lalić-Popović, Mladena (Archives of Pharmacy, 2022)
In recent years, the interest in 3D printing of medicines has increased due to many advantages of this technology, such as flexibility of the dose and dosage form of the printed product. Fused deposition modeling (FDM) is one of the most popular 3D printing technologies in the pharmaceutical field, due to its low cost and simplicity. The subject of this review is the potential use of natural products as biodegradable and biocompatible materials with good safety profiles in FDM 3D printing of pharmaceuticals. Natural products such as alginate, chitosan and starch have already been employed as excipients in FDM 3D printed pharmaceutical dosage forms, while others like shellac and zein show the potential, but haven’t yet been part of 3D printed pharmaceutical formulations. These excipients have different roles in the formulation of filaments for FDM 3D printing, for example as fillers, matrix carriers or drug-release modifiers. In addition, the possibility of incorporating active pharmaceutical ingredients of natural origin in filaments for FDM 3D printing was reviewed. High printing temperatures limit the use of natural products in FDM 3D printing. However, adequate selection of thermoplastic material and printing parameters can widen the use of natural products in FDM 3D printing of pharmaceutical dosage forms.
Keywords: biopolymers; natural fillers; natural plasticizers; FDM; three-dimensional printing